2020
DOI: 10.3892/mmr.2020.11268
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA HOTAIR promotes burn wound healing by regulating epidermal stem cells

Abstract: local transplantation of epidermal stem cells (eScs) exerts a therapeutic effect on burn wounds. However, cell viability can impede their clinical application. HoX antisense intergenic rna (HoTair) is involved in regulating adult tissue stem cells, as well as in developmental patterning and pluripotency. However, little is known about its role in regulating eScs. The present study was performed to investigate the effects of HoTair in the modulation of eScs and wound repair. Firstly, reverse transcription-quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…However, large‐area scars were still visible and no dermal layer began to form in Blank group, indicating that the chronic nonhealing wounds induced by deep second‐degree burns cannot self‐repair in 14 days. [ 31 ] Previous studies proved that the complete healing in deep second‐degree burn wounds model needs to take more than 25 days. [ 32 ] Therefore, H&E staining results demonstrated that PCL+5ZS nanofibrous scaffolds could effectively accelerate the wound healing process and promote re‐epithelialization, exhibiting great potential for promoting burns wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…However, large‐area scars were still visible and no dermal layer began to form in Blank group, indicating that the chronic nonhealing wounds induced by deep second‐degree burns cannot self‐repair in 14 days. [ 31 ] Previous studies proved that the complete healing in deep second‐degree burn wounds model needs to take more than 25 days. [ 32 ] Therefore, H&E staining results demonstrated that PCL+5ZS nanofibrous scaffolds could effectively accelerate the wound healing process and promote re‐epithelialization, exhibiting great potential for promoting burns wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…The ephrin receptor signaling pathway, which is important in wound closure and healing [ 67 ], is strongly activated as early as 1 day post treatment followed by a gradual decrease over the 28-day treatment period. The long non-coding RNA HOTAIR regulatory pathway was also activated following fractional laser treatment as would be required for proper wound healing [ 68 ]. Additionally, the large changes in S100 gene expression at 1 day post fractional laser treatment, along with the rapid induction of gene expression of several inflammatory pathways, confirms a quick immune response to the damage and greatly expands previous histochemical study findings [ 42 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ephrin receptor signaling pathway, which is important in wound closure and healing (Nunan et al, 2015), is strongly activated as early as 1 day post treatment followed by a gradual decrease over the 28-day treatment period. The long non-coding RNA HOTAIR regulatory pathway was also activated following fractional laser treatment as would be required for proper wound healing (Shi et al, 2020). Additionally, the large changes in S100 gene expression at 1 day post fractional laser treatment, along with the rapid induction of gene expression of several inflammatory pathways, confirms a quick immune response to the damage and greatly expands previous histochemical study findings (Prignano et al, 2009;Helbig et al, 2011;Xu et al, 2011;Prignano et al, 2012;Helbig et al, 2009;El-Domyati et al, 2007;Zheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%